Prevalence of tuberculosis among prisoners in sub-Saharan Africa: a systematic review and meta-analysis - Sisay Asgedom, Yordanos; Ambaw Kassie, Gizachew; Melaku Kebede, Tsegaye (Frontiers in Public Health, 2023)
Background: Tuberculosis (TB) is a key community health problem in numerous settings, predominantly in sub-Saharan Africa (SSA). TB is the second most lethal infectious disease worldwide. Around 1.6 million people died in 2021. TB prevention and control strategies are difficult to implement in prison, especially in sub-Saharan Africa, owing to overcrowding and poor ventilation. Thus, this systematic review and meta-analysis aimed to synthesize the estimated pooled prevalence of tuberculosis among prisoners in sub-Saharan Africa.: Electronic biomedical databases such as Google Scholar, Web of Science, PubMed/Medline, EMBASE, and Science Direct were used to systematically explore candidate studies published until December 2022. Data extraction was performed using a Microsoft Excel spreadsheet. The estimated pooled prevalence of tuberculosis was determined using a fixed-effects model. Cochrane Q-test and I 2 statistics were used to check heterogeneity statistically across different studies. Begg's rank and Egger's tests were performed to assess evidence of possible publication bias.Results: Forty-two articles involving 59,300 60,845 prisoners were included in this systematic review and meta-analysis. The pooled prevalence of tuberculosis was 4.0206% (95% CI: 2.68-2.77-5.365.34). We found the highest prevalence by using Gene X pert as a diagnostic method which was 4.975.86 (95% CI: 2.2271-7.739.00). There is no evidence of publication bias.The outcome of this review revealed a high prevalence of tuberculosis among prisoners in sub-Saharan Africa. To reach the "End Tuberculosis strategy '' by 2030 early identification of cases through screening during their entry and periodical active case finding is